Contesting A Cultural Style (Makassar Painting And Local Socio-Cultural Adaptation) - Cita Pratiwi; Karta Jayadi; Arlin Adam; Abdul Ahmad (Indonesian Culture and Religion Issues, 2025)
This study aims to analyze: (1) the social mechanisms of contestation in the Makassar painting arena) ((2) the process of adaptation of local cultural symbols and values in the creative practice of Makassar painting) ((3) the social and artistic strategies of Makassar painters in negotiating local cultural authenticity with the demands of the art market) (and (4) the impact of art commodification on local cultural representation, symbolic meaning, and the sustainability of visual traditions. This study uses a qualitative approach with a case study design to gain an in-depth understanding of painting as a social practice. The research subjects are Makassar painters who are active in various art activities, supported by accompanying informants such as curators, academics, and art enthusiasts. Data was collected through in-depth interviews, observation, documentation, and analysis of artworks. To ensure data validity, this study uses source and method triangulation techniques. The results show that Makassar painting operates as an arena of symbolic contestation that is not yet fully institutionalized in a stable manner. In this arena, artistic legitimacy is formed through social relations, informal networks, and symbolic recognition mechanisms. Makassar painters adapt local Bugis-Makassar cultural symbols and values as part of their creative and social strategies to maintain their position in the art arena. The adaptation of local culture is not static, but rather undergoes a process of negotiation and transformation of meaning in line with the entry of the logic of the art market and the cultural industry.This study also found that the process of commodification of art influences the way local cultural symbols are represented in paintings. On the one hand, commodification opens up economic opportunities and the sustainability of art practices) (on the other hand, it has the potential to reduce the symbolic meaning of local culture to commercial value. Using Pierre Bourdieu's theory of practice, this study asserts that Makassar painting is a social practice that reflects the dialectical relationship between arena, habitus, and capital, and is a form of local socio-cultural adaptation in the context of contemporary society.